Cyclic friction-slip behaviour of G350-steel bolted connections - Lacey, Andrew; Chen, Wensu; Hao, Hong (Elsevier, 2023)
In this study, an experimental program was performed to investigate the cyclic friction-slip behaviour of AS/NZS 3678-350 (G350) steel with different surface finishes. Fifteen bolted steel connections consisting of EN 1090-2 slip factor test assemblies with M16 bolts were prepared and tested with five commonly used surface finishes including inorganic zinc silicate (IZS), epoxy zinc primer (EZP), aliphatic acrylic polyurethane (PUR), abrasive blasted (SA2), and clean mill scale (CMS). The first initial force-slip stiffness and the first slip factor are reported for each surface finish and compared with the existing literature and design standards. An empirical model is proposed to predict the initial slip behaviour based on the first slip factor and initial stiffness, and its accuracy is demonstrated for the coated and uncoated steel. The effects of the cyclic load are then considered, and the cyclic slip factor and initial stiffness are evaluated and discussed. Finally, corresponding empirical models are proposed for the cyclic slip factor and friction-slip stiffness as a function of the cumulative displacement.